Artificial Intelligence in Pharmacovigilance and COVID-19 - Bhardwaj, Kamini; Alam, Rabnoor; Pandeya, Ajay; Sharma, Pankaj K. (Current Drug Safety, 2023)
The history of pharmacovigilance started back 169 years ago with the death of a 15- year-old girl, Hannah greener. However, the Thalidomide incident of 1961 brought a sharp change in the pharmacovigilance process, with adverse drug reaction reporting being systematic, spontaneous, and regulated timely. Therefore, continuous monitoring of marketed drugs was essential to ensure the safety of public health. Any observed adverse drug reaction detected by signals was to be reported by the health profession. Moreover, signal detection became the primary goal of pharmacovigilance based on reported cases. Among various methods used for signal detection, the Spontaneous Reporting System was most widely preferred; although, it had the limitation of
Keywords: Spontaneous Reporting System (SRS)